Inhibitors of Plasminogen Activator in Neutrophils and Mononuclear Cells from Septic Patients - Haj, Montaser A; Robbie, Linda A; Adey, Gillian D; Bennett, Bruce (Thrombosis and Haemostasis, 1995)
Leucocytes, both polymorphs and mononuclear cells, play a variety of roles in the evolution of human response to sepsis, both local and generalised. In this study, inhibitors of plasminogen activator were measured in leucocytes from normal and septic patients. Plasminogen activator inhibitor-1 (PAI-1) was identified in polymorphs from normal individuals and levels rose significantly in polymorphs from septic patients: neutrophils from normal subjects did not contain PAI-2 but this protein was detectable in significant quantities in polymorph preparations from septic patients. In contrast, mononuclear cells from normal and septic patients contained no detectable quantities of PAI-1. Significant amounts of PAI-2 were present in normal mononuclear cells, and the levels rose significantly in monocytes from septic patients. PAI-2 is thus here identified in human subjects, distinct from those with pregnancy or malignancy, as playing a role in a pathological process. The increased levels of both inhibitors produced by leucocytes may clearly contribute directly to the persistence of fibrin, a characteristic feature of the response to infection, local or general; they may thus participate in successful localisation of infections (abscess formation etc.) and in the evolution of the major systemic complications of disseminated sepsis characterised by microvascular occlusion by fibrin such as renal failure, shock lung or digital ischaemia.